Antoni Zabłocki’s Description of the Stay of Catharine II and Joseph II in Cherson and Crimea in 1787 - Ciesielski, Tomasz (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
From July 1784 to mid-1792, a Polish trade and diplomatic post operated in Kherson (until the spring of 1788), and then in Mirgorod, in the Black Sea territories of the Russian Empire. From mid-1784 until the end of 1791, Antoni Zabłocki, a former soldier of the Crown Army, the Bar Confederate, and an exile in Russia, was the head of the facility, and from the summer-autumn 1786, the consul. He did not have any diplomatic preparation, and his qualifications were limited to the knowledge of the Russian language and the realities of social and economic life in the tsarist state, as well as to close contacts with the surroundings of King Stanisław August. This secured him a job as a royal agent in the region of the Russian Empire. During his six-and-a-half-year stay in the Black Sea area, Zabłocki initially conducted the typical activity of a trade agent – he informed the king and the Department of Foreign Interest about the economic situation in Kherson and in the south of Russia (including Crimea), the economic situation and prices of agricultural and forestry goods, as well as of Polish companies, and department stores. Probably already at the end of 1784, and certainly in 1785, Zabłocki assumed normal consular duties. As part of them, he issued travel passports and tried to take care of the subjects of King Stanisław August residing in the Black Sea territories (not only in Russia but also in the Ochakov eyalet of the Ottoman Empire), who came either in search of work or were selling agricultural and forestry goods. Zabłocki strove for the release of Poles imprisoned in Russia, he resolved private and public disputes between Russians and Poles, in relation to cross-border contacts. In his reports, Zabłocki devoted much attention to the political and social situation in the region, and especially to the progress in the colonization of the Black Sea territories of Russia, which had a significant impact on the demographic situation in the border provinces of the Commonwealth, as well as to the actions and plans of Prince Potemkin related to the development of territories under his authority. He formulated his comments and assessments on the basis of his own experience as well as observations of the work of representatives of other countries accredited in Kherson. Zabłocki was characterized by enormous perceptiveness, intuition, and the ability to interpret perceived facts and phenomena. In addition, he did not shy away from writing extensive reports, although in this case he can be accused of having too much faith in his own erudition with too little attention to linguistic correctness and a tendency to use Russianisms. These can be found in many letters, including the account of the stay of Catherine II and Joseph II in Kherson, which is an integral part of the article, and their joint tour of Crimea between 14 May and 13 June 1787. This account is an interesting source, mainly due to the colourful narrative and the descriptions of the events taking place in Kherson during the stay of the Empress and the Emperor.